Hospice at home--a new service for patients with advanced HIV/AIDS: a pilot evaluation of referrals and outcomes. - Koffman, J (1996)
Between 50 and 70% of patients with a terminal illness indicate a preference to remain at home for as long as possible until their death. Nevertheless, a much smaller percentage actually die at home in England and Wales. A new hospice-at-home service in North London for patients with HIV/AIDS is described in this report. Terminal care for HIV/AIDS patients can be provided at home by a multidisciplinary team which offers 24-hour care.